Ecosystem‐level controls on root‐rhizosphere respiration. Issue 2 (17th April 2013) - Hopkins, Francesca; Gonzalez‐Meler, Miquel A.; Flower, Charles E.; Lynch, Douglas J.; Czimczik, Claudia; Tang, Jianwu; Subke, Jens‐Arne
Summary: Recent advances in the partitioning of autotrophic from heterotrophic respiration processes in soils in conjunction with new high temporal resolution soil respiration data sets offer insights into biotic and environmental controls of respiration. Besides temperature, many emerging controlling factors have not yet been incorporated into ecosystem‐scale models. We synthesize recent research that has partitioned soil respiration into its process components to evaluate effects of nitrogen, temperature and photosynthesis on autotrophic flux from soils at the ecosystem level. Despite the widely used temperature dependence of root respiration, gross primary productivity (GPP) can explain most patterns of ecosystem root respiration (and to some extent heterotrophic respiration) at within‐season time‐scales. Specifically, heterotrophic respiration is influenced by a seasonally variable supply of recent photosynthetic products in the rhizosphere. The contribution of stored root carbon (C) to root respiratory fluxes also varied seasonally, partially decoupling the proportion of photosynthetic C driving root respiration. In order to reflect recent insights, new hierarchical models, which incorporate root respiration as a primary function of GPP and which respond to environmental variables by modifying C allocation belowground, are needed for better prediction of future ecosystem C sequestration.